O gênero Phyllanthus L. (Phyllanthaceae) na região sudeste do Brasil - Martins, Erika Ramos (2013)
The genus Phyllanthus L. is the largest and most diverse of the family Phyllanthaceae with about 830 species that are spread mainly throughout the tropics, of which 200 are in the neotropics. From 100 species occurring in Brazil, where the genre is richest in South America, 40% of them occur in the southern region of the country, where is located one of the centers of diversity of the genus. The great diversity, richness and taxonomy still little studied, even regarding the circumscription of their species, justifying this study. Thus, the main aim of this study was to survey and analyze morphological and taxonomic aspects of the genus in southern Brazil, contributing to the knowledge of Phyllanthus in the country as well to the Brazilian biodiversity. This study includes an identification key, descriptions and comments on the taxonomy, geographical distribution and illustrations of the species. In southeastern Brazil were found 37 species of the genus: Phyllanthus acuminatus Vahl., P. acutifolius Poir ex Spreng., P amarus Schumach., P. angustissimus Müll. Arg., P. arenicola Casar., P. augustinii Baill., P. avicularis Müll. Arg., P. caparaoensis G.L. Webster., P. caroliniensis Walter., P. choretroides Müll. Arg., P. cipoensis E.R. Martins & Cordeiro sp. nov. ined., P. cladotrichus Müll. Arg., P. dictyospermus Müll. Arg., P. fastigiatus Mart. ex Müll. Arg., P. gladiatus Müll. Arg., P. glaziovii Müll. Arg., P. heteradenius Müll.Arg., P. hypoleucus Müll. Arg., P. hyssopifolioides Kunth, P. itatiaiensis Brade., P. juglandifolius Willd., P. klotzschianus Müll. Arg., P. minutulus Müll. Arg., P. mocotensis G.L. Webster, P. niruri L., P. orbiculatus L.C. Rich., P. perpusillus Baill., P. pinifolius Baill., P. piranii G.L. Webster, P. riedelianus Müll. Arg., P. rosmarinifolius Müll. Arg., P. sellowianus (Klotzsch) Müll. Arg., P. stipulatus (Raf.) Webster, P. subemarginatus Müll. Arg., P. tenellus Roxb., P. umbratus Müll. Arg. and P. urinaria L.